2012
DOI: 10.1108/17410401211212670
|View full text |Cite
|
Sign up to set email alerts
|

An assessment of the critical success factors for Six Sigma implementation in Indian industries

Abstract: Purpose -The purpose of this paper is to present the results from an empirical investigation of Six Sigma status in Indian industry, especially to highlight critical success factors (CSFs) of Six Sigma implementation in a developing economy like India. Design/methodology/approach -The study is based on survey questionnaire suitable for Indian industries. The results of the study are based on descriptive statistics. Findings -The results of this exploratory empirical study reflect the impact of different CSFs o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
74
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(80 citation statements)
references
References 29 publications
2
74
0
4
Order By: Relevance
“…The results presented in this paper have concurred with theoretical research found in the literature that the most important LSS success and failure factors are top management commitment and resistance to change (Shokri et al, 2014;Thomas et al, 2014;Assarlind et al, 2013;Delgado et al, 2010;Desai et al, 2012;Choi et al, 2012;Jayaraman et al, 2012;Lee et al, 2011). In fact, this research study has emphasised the human behavioural-related aspects of these factors and more importantly revealed key human resource elements to support LSS implementation.…”
Section: Research and Practical Implicationssupporting
confidence: 77%
“…The results presented in this paper have concurred with theoretical research found in the literature that the most important LSS success and failure factors are top management commitment and resistance to change (Shokri et al, 2014;Thomas et al, 2014;Assarlind et al, 2013;Delgado et al, 2010;Desai et al, 2012;Choi et al, 2012;Jayaraman et al, 2012;Lee et al, 2011). In fact, this research study has emphasised the human behavioural-related aspects of these factors and more importantly revealed key human resource elements to support LSS implementation.…”
Section: Research and Practical Implicationssupporting
confidence: 77%
“…The majority of the measures being tried by them are efcient enough of producing the desired results but trouble remain with their implementation and longer time span to realize the benets. The requirement is for a break through strategy, which can deliver multidirectional benets in relatively shorter duration of time (Desai, Antony, & Patel, 2012). "Medium Small and Micro Enterprises (SMEs) have always been the backbone of an economy in general and secondary sector in particular.…”
Section: Introductionmentioning
confidence: 99%
“…(Erdogan and Canatan, 2015;Desai, et al, 2012). LSS has been widely associated with large manufacturing firms like Motorola, who was the first to introduce the concept of Six Sigma.…”
Section: Introductionmentioning
confidence: 99%